2014
DOI: 10.1115/1.4027389
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics of an Inclined Impinging Jet on a Curved Surface in Crossflow

Abstract: This study reports on heat transfer characteristics on a curved surface subject to an inclined circular impinging jet whose impinging angle varies from a normal position 9 = 0 deg to 9 = 45 deg at a fixed jet Reynolds number of Rej = 20,000. Three curved surfaces having a diameter ratio (DIDfl of 5.0, 10.0, and infinity (i.e., a flat plate) were selected, each positioned systematically inside and outside the potential core of jet flow where Dt is the circular jet diameter. Present results clarify similar and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies have shown that the curvature of a cylinder affects the thickness and velocity field of a liquid film, thereby affecting heat transfer. Wang et al [20][21][22] studied the surface heat transfer characteristics of a single jet and multiple jets impinging on a cylinder with a constant heat flux density, and they analyzed the changes in the local Nusselt number caused by the transition from laminar flow to turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the curvature of a cylinder affects the thickness and velocity field of a liquid film, thereby affecting heat transfer. Wang et al [20][21][22] studied the surface heat transfer characteristics of a single jet and multiple jets impinging on a cylinder with a constant heat flux density, and they analyzed the changes in the local Nusselt number caused by the transition from laminar flow to turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers has conducted several studies on composite cooling technique since the 1980s. Wang achieved many success on researching compound cooling technique [7,8]. Yang [9] investigated the composite cooling behavior of the impinging jet in the solidification section.…”
Section: Introductionmentioning
confidence: 99%